Analisis Strategis Rukita Winter - Sugiarto, Yonatan Stenly; Alwi, Muhammad Yusup; Ibrahim, Muhammad Satrio Hilmiawan; Tiarapuspa; Survia, Desty (Jurnal Ilmiah Aset, 2024)
Rukita as a boarding house service provider is one of the main players in fulfilling the housing needs of students, workers, and the general public. With the tight competition in the boarding house market, especially in metropolitan areas such as West Jakarta, Rukita Winter has its own challenges to ensure its excellence and competitiveness. Successfully attracting the attention of boarding house tenants requires the right action in business strategy. Therefore, Rukita Winter always strives to adjust its business strategy to meet the needs and preferences of boarding house tenants. This study aims to identify and analyze the business strategies implemented by Rukita Winter. In addition, this study also aims to analyze the strengths (Strengths), weaknesses (Weaknesses), opportunities (Opportunities), and threats (Threats) faced by Rukita Winter's business. The method used involves the use of the IFE (Internal Factor Evaluation), EFE (External Factor Evaluation), IE (Internal-External), and QSPM (Quantitative Strategic Planning Matrix) matrices to analyze Rukita Winter's position. This study is expected to contribute to increasing knowledge and understanding of SWOT analysis and how its application can help Rukita Winter in formulating business strategies.